PENGEMBANGAN MODUL PEMBELAJARAN IPA BIOLOGI BERORIENTASI PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI STRUKTUR TUMBUHAN DAN PEMANFAATANNYA DALAM TEKNOLOGI DI KELAS VIII SMP - Syovia Heryeni; Mariani Natalina; Wan Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of this study is the development learning module biology ipa scientific oriented approach for improved critical thinking on the structure of plants and materials utilization in technology in class VIII SMP. The research was conducted at the campus of the University of Riau FKIP Biology Education and Student responses conducted in SMP Negeri 1 Pekanbaru in March to December 2015. This study uses 4-D model of development. Stages 4-D consists of four stages, namely Define (Definition Phase), Design (Stage Design), Develop (Development Phase), and Disseminate (Phase dissemination of). Data collection instruments used were sheets of validation and student questionnaire responses. Sheets validation judged by five validator which is composed of three lecturers and two junior high school teacher that consists of four aspects: the feasibility of the content, language, and kegrafisan dish. Results of the study the average score for the validation of the feasibility aspects of the content, language, serving and kegrafisan on module to obtain an average score of 3.4 with very valid category. Feasibility aspects contents obtained an average score of 3.5 in the category of very valid, linguistic aspects obtained a score of 3.4 with very valid category, next to the aspect grain obtained a score of 3.4 category is very valid, and aspects kegrafisan obtain an average score of 3, 3 categories are very valid. While the average score of students' responses to a questionnaire developed module is 3.4 to excellent category, out of 20 students in mind that 14 students responded very well to the module-oriented scientific approaches and 6 students responded well to the module-oriented approach scientifically developed. It was concluded that biological science learning modules oriented scientific approach that has been developed can be used and tested by teachers as an alternative in learning activities.Keywords: Critical thinking, Development, Module, Scientific Approach